جماليات علم البديع في خطبة بيعة عليّ بن أبي طالب (رضي الله عنه) في كتاب نهج البلاغة - Abdulmunim Abdullah Khalaf; Moh Rofiq Sholehudin; Nasywa Nur Rahmania; Hanik Mahliatussikah (PPPBA, 2025)
This study aims to analyze the function of applying Ilm al-Badiʿ (both muhassinat lafdziyyah and maʿnawiyyah) in Sermon [16] of Nahj al-Balaghah, commonly known as the Sermon of the Pledge (Khutbah Baiʿat) of Ali ibn Abi Talib. The research employs a descriptive qualitative method with a rhetorical content analysis (balaghiyyah) approach. The findings reveal a dominant use of contrastive techniques (tibaq and muqabalah) and phonetic techniques (jinas and sajaʿ). The muhassinat maʿnawiyyah primarily function as tools of dramatization to emphasize moral dichotomies (such as al-haqq versus al-batil), while the muhassinat lafdziyyah serve to create a climactic rhythm that reinforces the urgency and authority of the message. Therefore, it can be concluded that Ilm al-Badiʿ is employed instrumentally by Ali ibn Abi Talib as a communication strategy to strengthen the prophetic message and to construct moral and leadership authority.